Facebook's Influence on Omni-channel Retailing (International Journal of Innovative Research in Engineering & Management, 2021)
From kirana shop retailing to internet retailing (i.e., rural to  urban), the Indian retailing sector has evolved. This situation was  disorganized at first, but it is now evolving into Omnichannel  commerce through Social Media (Facebook). The goal of this  research is to provide a more intelligent shopping experience on  social media, particularly on Facebook. The Random Sampling  technique was used to gather data from 1045 respondents using  the Structured Questionnaire. Madurai Engineering Students and  Staff are among the responses. The data was analyzed using  Statistical Software (SPSS), with simple percentages, descriptive  statistics, and ANOVA being utilized to analyze the data. This  research provides a comprehensive explanation and analysis of  how Facebook affects the business dynamics of retailers.
Keywords: Facebook marketing; Omni-channel; Online purchasing; Digital Retailing; Social networking sites